Pemetaan Investasi Syariah dalam Mengurangi Kerugian bagi Investor Pemula - Bayu Purnomo; Ahmad Faisal Tanjung; Nur Hidayah Batubara; Paisal Rahmat (Pusat Riset dan Inovasi Nasional, 2025)
Shariah-based investments are increasingly in demand in Indonesia along with the increasing awareness to invest according to Islamic principles, such as being free from usury, gharar and maysir. However, low financial literacy is an obstacle in choosing the right instrument, especially for novice speculators. This study aims to identify the right type of Islamic investment and its selection criteria. The method used is a literature study with a qualitative descriptive approach, analyzing various academic and relevant sources. The results showed that Islamic mutual funds, sukuk, and gold are the most appropriate instruments because they are low-risk, affordable, and in accordance with sharia principles. The findings are expected to be an educative reference to improve financial literacy and encourage public participation in sustainable halal investment.